Choice of primary and secondary outcomes in randomised controlled trials evaluating treatment for uterine fibroids: a systematic review. (14th October 2021) - Amoah, A; Chiu, S; Quinn, SD
Abstract : Background: Core outcome sets aim to reduce research heterogeneity and standardise reporting, allowing meaningful comparisons between studies. Objectives: To report on outcomes used in randomised controlled trials (RCTs) investigating uterine fibroid treatments, towards the development of a core outcome set for fibroid research. Selection strategy: Database search of MEDLINE, PubMed, EMBASE and CINAHL (inception to July 2021) for all English‐language RCTs involving surgical or radiological fibroid treatments. Data collection and analysis: A total of 1885 texts were screened for eligibility by two reviewers independently according to PRISMA methodology. JADAD and Management of Otitis Media with Effusion in Cleft Palate (MOMENT) scores were used to assess methodological and outcome reporting quality of studies, respectively. Outcomes were mapped to nine domains. Non‐parametric tests for correlation and to compare group medians were undertaken. Main results: There were 23 primary outcomes (23 outcome measures) and 173 secondary outcomes (95 outcome measures) reported in 60 RCTs (5699 participants). The domains with highest frequency of primary outcomes reported were bleeding and quality of life (QoL). The most frequent primary outcomes were postoperative pain, QoL and menstrual bleeding. No primary outcomes were mapped to fertility domains. Median MOMENT outcome score was 5 (interquartile range 3). There was correlation between MOMENT outcome score and JADAD scores ( r  = 0.491, P  = 0.0001), publishing journal impact factor ( r  = 0.419, P  = 0.008) and publication year ( r  = 0.332, P  = 0.01). Conclusion: There is substantial variation in the outcomes reported in fibroid RCTs. There is a need for a core outcome set for fibroid research, to allow improved understanding regarding the effects of different treatments. Tweetable abstract: There is substantial variation in outcomes reported in uterine fibroid randomised controlled trials. Tweetable abstract: There is substantial variation in outcomes reported in uterine fibroid randomised controlled trials.